The effect of pharmacist-led medication therapy management in the multidisciplinary care of acute kidney injury survivors - Ting Wang; Hao-Cheng Kang; Chien-Chih Wu; Tsung-Lin Wu; Chih-Fen Huang; Vin-Cent Wu (The Korean Society of Nephrology, 2024)
Background The Acute Disease Quality Initiative advocates multidisciplinary care for the survivors of acute kidney injury (AKI). The bundled care strategy recognizes the role of pharmacists. However, their specific contributions in this context remain underexplored. Methods This retrospective study examined the efficacy of pharmacist-led post-AKI pharmaceutical care in outpatient settings at a single center. Adults with recent AKI during hospitalization, maintaining an estimated glomerular filtration rate <45 mL/min/1.73 m2 postdischarge, were enrolled in a multidisciplinary team care program from March 2022 to January 2023, with a 6-month follow-up period. Pharmacist-delivered care adhered to international multidisciplinary consensus guidelines. Efficacy was evaluated by analyzing medication-related recommendations, medication adherence, nephrotoxic drug utilization, and renoprotective medication usage before and after the intervention. Results A total of 40 patients were referred to the pharmacist-managed clinic. Of these, 33 patients (mean age, 63 ± 15 years; 60.6% male) attended the clinic. Nineteen patients completed follow-up visits. The pharmacist provided 14 medication-related recommendations to relevant physicians, with 10 of these recommendations (71.4%) being accepted. There was a significant decrease in the use of modifiable nephrotoxic drugs (p = 0.03). However, no significant improvements were noted in medication adherence or the utilization of renoprotective medications. Conclusion Our study underscores the potential benefits of pharmacist-led post-AKI bundled care strategy in outpatient settings. We observed a significant reduction in the utilization of modifiable nephrotoxic drugs, indicating the effectiveness of pharmacist interventions in optimizing medication regimens to mitigate renal harm.